2012
DOI: 10.1016/j.cognition.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The gestures ASL signers use tell us when they are ready to learn math

Abstract: The manual gestures that hearing children produce when explaining their answers to math problems predict whether they will profit from instruction in those problems. We ask here whether gesture plays a similar role in deaf children, whose primary communication system is in the manual modality. Forty ASL-signing deaf children explained their solutions to math problems and were then given instruction in those problems. Children who produced many gestures conveying different information from their signs (gesture-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
0
42
0
6
Order By: Relevance
“…Goldin-Meadow, Shield, Lenzen, Herzig and Padden (2012) tested these possibilities in 40 ASL-signing deaf children asked to explain their solutions to math problems and then given instruction in those problems. Children who produced many gestures conveying information not found in the signs the gestures accompanied (i.e., gesture-sign mismatches) were more likely to succeed after instruction than children who produced few, suggesting that mismatch can occur within-modality, and that within-modality mismatch predicts learning just as across-modality mismatch does.…”
Section: Mimetic Encoding Is Important To Human Communication and Is mentioning
confidence: 99%
“…Goldin-Meadow, Shield, Lenzen, Herzig and Padden (2012) tested these possibilities in 40 ASL-signing deaf children asked to explain their solutions to math problems and then given instruction in those problems. Children who produced many gestures conveying information not found in the signs the gestures accompanied (i.e., gesture-sign mismatches) were more likely to succeed after instruction than children who produced few, suggesting that mismatch can occur within-modality, and that within-modality mismatch predicts learning just as across-modality mismatch does.…”
Section: Mimetic Encoding Is Important To Human Communication and Is mentioning
confidence: 99%
“…Even more important from the point of view of our discussion here, the more gesture-sign mismatches signers produced in their problem-solving explanations prior to instruction, the more likely they were to profit from the lesson and solve the problems successfully after instruction [97]. It thus appears to be gesture's ability to introduce a second representational format that is key to its success in predicting learningmismatch can predict learning whether the categorical information is conveyed in the manual (sign) or oral (speech) modality.…”
Section: (Iv) Narrativesmentioning
confidence: 99%
“…Goldin-Meadow et al [97] explored this question in 40 ASLsigning deaf children and found, first, that the child signers produced gestures along with their signed explanations as often as hearing children produced gestures along with their spoken explanations on these problems. Moreover, the signers produced gesture-sign mismatches as often as the hearing children produced gesture-speech mismatches.…”
Section: (Iv) Narrativesmentioning
confidence: 99%
“…For example, there appear to be differences between the signing of deaf children of deaf parents and hearing children of deaf parents, both of whom learn ASL as a first language (Brentari et al 2012b). Finally, researchers have asked whether signers gesture (Duncan 2005) and, if so, whether cosign gesture serves the same cognitive functions as cospeech gesture (Goldin-Meadow et al 2012). The large number of potential areas of crossover abilities between cospeech gesture and sign offers opportunities to explore the set of manual abilities that are ultimately exploited for grammatical purposes in emerging and established sign languages (see Goldin-Meadow & Brentari 2016 for further discussion).…”
Section: Surprising Results and Further Implications Of Work On Lamentioning
confidence: 99%